Abscisic acid and its role in the modulation of plant growth, development, and yield stability - Kavi Kishor, Polavarapu B.; Tiozon, Rhowell N.; Fernie, Alisdair R.; Sreenivasulu, Nese (Elsevier, 2022)
Abscisic acid (ABA) is known to confer stress tolerance; however, at elevated levels it impairs plant growth under prolonged stress. Paradoxically, at its basal level, ABA plays many vital roles in promoting plant growth and development, including modulation of tillering, flowering, and seed development, as well as seed maturation. In this review, we provide insight into novel discoveries of ABA fluxes, ABA signaling responses, and their impact on yield stability. We discuss ABA homeostasis implicated under pre- and postanthesis drought and its impact on productive tillers, grain number determination, and seed development to address yield stability in cereal crops while considering the new knowledge that emerged from the model plant systems.